2021
DOI: 10.1002/adem.202100022
|View full text |Cite
|
Sign up to set email alerts
|

Insulating Paper Cellulose with High Mechanical Performance and Low Polarizability: The Effect of Doping Concentration on Polyhedral Oligomeric Silsesquioxanes‐Modified Cellulose

Abstract: To study the effect of doping concentration on polyhedral oligomeric silsesquioxane (POSS)‐modified cellulose and its internal mechanism, molecular dynamics is used to establish a pure cellulose model and 1, 2, 3, 4, and 5 wt% POSS‐modified cellulose models, and the cohesive energy density and solubility parameter, mechanical properties, free volume, mean square displacement, and polarizability are calculated at 343 K. The simulation results show that the addition of POSS effectively improves the compatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In 2021, Yang [48] et al used polyhedral oligomeric silsesquioxane (POSS) modified insulating paper to investigate the optimum addition mass fraction of POSS. They found that when the mass fraction of POSS was 3%, the elastic modulus, shear modulus and bulk modulus pressure of insulating paper were improved by 19.96%, 20.52% and 22.19%, respectively.…”
Section: Other Modification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, Yang [48] et al used polyhedral oligomeric silsesquioxane (POSS) modified insulating paper to investigate the optimum addition mass fraction of POSS. They found that when the mass fraction of POSS was 3%, the elastic modulus, shear modulus and bulk modulus pressure of insulating paper were improved by 19.96%, 20.52% and 22.19%, respectively.…”
Section: Other Modification Methodsmentioning
confidence: 99%
“…In 2021, Yang [48] et al. used polyhedral oligomeric silsesquioxane (POSS) modified insulating paper to investigate the optimum addition mass fraction of POSS.…”
Section: Research Progress Of Modified Cellulose Insulating Papermentioning
confidence: 99%
See 1 more Smart Citation